ROLE OF CLAMPING TUBE THORACOSTOMY PRIOR TO REMOVAL IN NON-CARDIAC THORACIC TRAUMA - Rasheed, Muhammad Asif; Majeed, Farhan Ahmed; Shah, Syed Zahid Ali; Naz, Aneeqa (Journal of Ayub Medical College Abbottabad, 2016)
Background: The frequently encountered thoracic trauma in surgical emergencies is a major cause of mortality and morbidity. Eighty percent of thoracic trauma can be managed by simple insertion of tube thoracostomy. Though guidelines for insertion are comprehensively explained in literature, an ideal algorithm for discontinuation is not available. A standard and safe defined protocol would eliminate hesitancy in confident removal among general surgeons. The objective of this study was to determine role of clamping trial prior to removal in terms of frequency of recurrent pneumothorax. Methods: This study was conducted in department of Surgery Combined military hospital/Military Hospital Rawalpindi from April 2013 to March 2014. Total 180 patients with blunt or penetrating thoracic trauma were included in the study. Chest tube (28-36 Fr) was inserted in Trauma centre under strict asepsis. Tubes were then connected to under water seal for minimum six hours. Patients were randomly divided in two equal groups (90 in each). In Group A, Clamping trial was given before attempting removal while in Group B, tube was removed immediately without clamping trial. Patients of both groups were observed two hourly for development of recurrent pneumothorax. Data was analysed using SPSS-18. Results: The comparison of frequency of recurrent pneumothorax in Group A (9 patients, 10%) and in Group B (4 patients, 4.5%) was not found to be statistically significant. (p-value 2.073). Conclusion: Clamping trial is unnecessary prior to removal of tube thoracostomy in blunt and penetrating non-cardiac thoracic trauma in terms of recurrent pneumothorax.